The impact of aging on future healthcare expenditure - Lukas Steinmann; Harry Telser; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2006)
The impact of aging on healthcare expenditure (HCE) has been at the center of a prolonged debate. This paper purports to shed light on several issues. First, it presents new evidence on the relative importance of the two components of HCE that have been distinguished by Zweifel, Felder and Meier (1999), viz. the cost of morbidity and the cost of mortality (their red herring hypothesis claims that neglecting the mortality component results in excessive estimates of future growth of HCE). Second, it takes account of recent evidence suggesting that HCE does increase life expectancy, implying that time-to-death is an endogenous determinant of HCE. Third, it investigates the contribution of population aging to the future growth of HCE. For the case of Switzerland, it finds this contribution to be relatively small regardless of whether or not the cost of dying is accounted for, thus qualifying the red herring hypothesis.
Keywords: J14; I12; 330; Health econometrics; Aging; Cost of dying; Healthcare expenditure; Gesundheitskosten; Sterblichkeit; Schätzung; Schweiz; Alternde Bevölkerung